Freedom and democracy: construction of human emancipation in Paulo Freire - Zanezi Peres, Sonia Maria; Rincon Afonso, Lucia Helena [UNESP]; Peres, Gleison Peralta (Univ Nove Julho, 2022)
Paulo Freire presented, in his period of experience, issues relevant to education, when he approached liberating and participatory practices. Paulo Freire seeks to explain by showing us that it was not possible to talk about liberating education, without pointing out the concept of liberating pedagogy. Given this scenario, we carried out a bibliographic research, with the objective of understanding through literature, exemplifying some elements of understanding in an approach to education, freedom and democracy. We seek to present the results of Paulo Freire's general ideas and the relationship of men and women in our society, the impacts of his writings and reflections on education during his intellectual trajectory recognized worldwide.
Keywords: popular education; human emancipation; democracy; freedom